MEDIA COMPANY'S STRATEGIC ANALYSIS USING BALANCE SCORECARD - Ardi Ardi; Jacob Donald Tan; Irwanto Halim; Teddy Purnama; Yuma Luqman Adhli (Milestone: Journal of Strategic Management, 2023)
The three steps of Media Innovation are focusing on optimizing TikTok, implementing a fair usage policy (FUP), and working strategically with Starlink. Optimization of TikTok aims to optimize digital marketing campaigns; the application of FUP includes regulations governing the fair use of internet bandwidth. And use Starlink satellite technology to expand the market. External adjustments in communication, branding, and interaction with customers and stakeholders. All activities and initiatives can be monitored by applying the balanced scorecard to measure media performance by considering four perspectives. Qualitative research methods through document studies to discuss the use of the balanced scorecard in dealing with external influences, analyze the industrial environment, discover internal strengths and weaknesses, and develop creative strategies and appropriate action plans, as well as change management to become the basis for implementing the desired changes for overall company performance measurement.